3 (s - 2) (s + 2)
are you just having people do your homework for you? you ought to be perfectly capable of this, it's very simple factoring.
2006-12-30 06:45:16
·
answer #1
·
answered by Shanny 2
·
1⤊
0⤋
3s^2-12=0
3s^2= 12
s^2= 4
s= 2 or -2
2006-12-30 14:46:13
·
answer #2
·
answered by 7
·
0⤊
2⤋
3s^2-12=0
3s^2=12
s^2=4
s=2
2006-12-30 14:45:36
·
answer #3
·
answered by Suhas 2
·
0⤊
1⤋
3(s-2)(s+2)
2006-12-30 14:53:26
·
answer #4
·
answered by Jon 3
·
0⤊
0⤋
3s² - 12 = 0
3(s - 2)( s + 2)
- - - - - - - - - -
3s² - 12 + 12 = 0 + 12
3s² = 12
3s² / 3 = 12 /3
s² = â4
s = ± 2
- - - -
s = 2
s = - 2
- - - - - - - -s-
2006-12-30 15:32:38
·
answer #5
·
answered by SAMUEL D 7
·
0⤊
2⤋
3(s - 2)(s + 2)
2006-12-30 14:56:01
·
answer #6
·
answered by stewartlucas467 2
·
0⤊
1⤋
This is a simple pre-algebra question, you should be able to do it but anyways here is the answer:
Look for like terms when simplfying a two term expression, in this case it is 3, so:
3 (s^2-4)
At this point you might think that you can't simplyfy it anymore but yes you can using the two therm square rule as I like to call it. Here it is
(a+b)(a-b)=a^2-b^2
and
sqrt(s^2)=s
sqrt(4)=2
so
3s^2-12= 3(s+2) (s-2)
2006-12-30 15:29:47
·
answer #7
·
answered by lulu 3
·
0⤊
1⤋
3s²-12 =
3s (s - 2)(s+2)
<>:<
2006-12-30 17:21:18
·
answer #8
·
answered by aeiou 7
·
0⤊
1⤋
3(s^2-4)
3(s+2)(s-2)
2006-12-30 14:46:02
·
answer #9
·
answered by miinii 3
·
0⤊
1⤋
3s^2-12
3(s^2-4)
3(s+2)(s-2)
2006-12-30 15:01:48
·
answer #10
·
answered by yupchagee 7
·
0⤊
1⤋